If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2 = 6 + -2x Reorder the terms: -2 + 8x = 6 + -2x Solving -2 + 8x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -2 + 8x + 2x = 6 + -2x + 2x Combine like terms: 8x + 2x = 10x -2 + 10x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 -2 + 10x = 6 + 0 -2 + 10x = 6 Add '2' to each side of the equation. -2 + 2 + 10x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 6 + 2 10x = 6 + 2 Combine like terms: 6 + 2 = 8 10x = 8 Divide each side by '10'. x = 0.8 Simplifying x = 0.8
| 15(2)-3(7)= | | x+x=5*x | | 4-3s+2(5.5)=9 | | 9y-7=6x+15 | | 12b+-8b= | | 20=16+4x | | y^2+80=144 | | 5(y)=40 | | -16x-9=-74 | | -5y+8x=14 | | 8(x-8)-6(x-1)+9x= | | -28n-3=4n | | 12b+-8= | | 10x^3+13x^2-103x+20=0 | | 4x+16-3x=-6-13 | | 9q+10=110 | | 12.67+42.35x=5.34x+26.85 | | -9x-49=-11x+23 | | 4x^5+x^4+4x^3+x^2=0 | | -x-9z+2z+7= | | 2(y-10)=10+2y | | 8x-3-4x=3(8x-1) | | x^2+13x+36=f(x) | | 8x-5y=14 | | -7x+3+8x=-10+25 | | 122+34=4 | | 3(-2-4x)=18 | | 7x-276=84-x | | -8x-9=8 | | 4x-40=3x+5 | | 1.25=-3w | | 4x+.5=54 |